Implementation of the Independent Learning Curriculum in Science Learning through Web Learning-Based Teaching Materials - Zakaria Zakaria; Mukhlidi Muskhir; Ambiyar Ambiyar; Riki Mukhaiyar (Postgraduate, University of Mataram, 2025)
This research is motivated by advances in science and technology, as well as the lack of variation in learning methods integrated with technology in learning. The purpose of this study is to determine the feasibility of web learning in supporting independent learning. The research method used is Research and Development (R&D) with the ADDIE development model which includes five stages, namely analysis, design, development, implementation, and evaluation. Validation was carried out by media experts and material experts, followed by a field trial involving 35 students of SMKN 1 Bintan Utara. The research instrument used a structured questionnaire on a Likert scale to assess the validity, practicality, and effectiveness of the media. The validation results showed that the learning media was valid and in accordance with learning needs. The practicality test produced an average score of 85.71% with a very practical category. The effectiveness test through gain score analysis showed an increase in student learning outcomes with a gain value of 0.6 with a moderate category. In conclusion, web-based learning materials are effective, valid, and practical in improving students' understanding of concepts and learning outcomes in science subjects